Assessment of Land Suitability for Enhancing Key Crop Commodities: Pineapple, Coffee, and Mango - Maroeto Maroeto; Rossyda Priyadarshini; Agung Winarno; Ken Bening Jiwa Jeni; Alexandra Neovita Tanaya (The University of Lampung, 2024)
This study aims to evaluate land suitability for enhancing the production of key crop commodities in Ngancar District, Kediri Regency, particularly pineapple, coffee, and mango. The district has high soil fertility potential due to its location at the foot of Mount Kelud. The research methods include land surveys, soil sampling at depths of 0-30 cm and 30-60 cm, and laboratory analysis to measure soil physical and chemical properties. Results indicate that the land in the study area generally falls into the marginal suitability class (S3), with the main limiting factors being soil texture dominated by sandy loam, low K₂O levels, and high rainfall that affects pineapple growth. Slope gradient is also a limiting factor for coffee and mango cultivation. Adjustments in soil management, such as timely fertilization and planting crops with strong root systems, can improve the land's suitability potential. In conclusion, although the land in Ngancar District has certain limitations, optimizing land use can enhance the productivity of key commodities, particularly through improved soil management and appropriate fertilizer use. Keywords: Crop commodities, Land Assessment, Land Degradation, Mount Kelud.